Retrospective Analysis of Spinal Anesthesia for Daycare Surgery during the COVID-19 Pandemic - Bhattarai, Prajjwal Raj; Khadka, Bikash; Adhikari, Hemant; Khadka, Rinku; Sharma, Apurb (Birat Journal of Health Sciences, 2022)
Introduction: We preferred general anesthesia over spinal anesthesia for day care surgeries in our center. During COVID-19 pandemic, we planned subarachnoid blocks for daycare surgeries, to minimize aerosol generation and to reduce virus transmission risk to health care professions.Objectives: This study intended to compare time of discharge after  subarachnoid block with general anesthesia in day care surgeries. We compare time to achieve post-anesthetic discharge score (PADS) equal to or more than nine; need for overnight hospitalization; and complications.Methodology: A retrospective analysis of cases posted for elective daycare surgery in our institute during COVID-19 pandemic from April 2020 to July 2020 were identified. We compared  time to  discharge home in patients who received general anesthesia and spinal anesthesia. Normality of distribution was determined using Two sample Kolmogorov-Smirnov Tes. Student t test was used for normally distributed data, Mann-Whitney U test was used for non-normal distributed data. Categorical variables were analyzed using a chi-squared or Fisher’s exact test. Results: A total of 2214 patients were included in this study.181 patients remained for analysis; 70 in the general anesthesia group and 91  in the spinal anesthesia group. Mean time (+SD) to achieve PADS score in group GA is 263.47(+75.06) whereas in group SAB was 339.55(+156.903). Mean time (+SD) taken to discharge home in group GA was 296.08(+74.76) whereas in group SAB was 365.66(+158.68) minutes respectively. Post hoc power of the study was 95.8.Conclusion: With low dose bupivacaine, spinal anesthesia is a safe alternative for ambulatory day care surgeries.